Assessing the impact of electricity production on industrial and agricultural output growth in Nigeria - Imisi Aiyetan; Adeleke Aremo; Phillip Akanni Olomola (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2020)
Purpose: While the relationships between energy or electricity consumption and economic growth are of great interest to economists, previous studies have not examined the dynamic effect of electricity production on industrial and agricultural output growth in Nigeria; this study attempts to fill the gap. This study thus investigates the dynamic effects of electricity production from renewable and non-renewable energy sources on industrial and agricultural output growth in Nigeria. Design/methodology/approach: This study disentangled electricity production by source - into renewable and nonrenewable - and employed a Structural Vector Autoregressive (SVAR) and other time series econometrics analysis. Findings: This study found that electricity production from both sources has a slight impact on the growth of the Nigerian industrial and agricultural sectors. In addition, this study supports the existing claim that economic growth and energy are linked and thus disproves the neo-classical assumption of the neutrality hypothesis. Research limitations/implications: This study considers annual data for all the variables due to the available data frequency for electricity production. However, the study assesses the validity of the estimated SVAR, and the results show that the analysis is robust for this study. Originality/value: This study contributes to the existing empirical literature by disentangling electricity production into renewable and non-renewable- and then examine their impacts on the crucial sectors of the Nigerian economy. This study shows that electricity production from the two energy sources contributes marginally to the growth of the industrial and agricultural sectors in Nigeria. Therefore, among other policy prescriptions, the author recommends that acceleration of projects that focus on off-grid electricity production under the Nigerian Energy Support Program (NESP) could minimize the current challenges of electricity production and its impact on the economy.
Keywords: Q40; Q30; 330; Structural VAR Industrial output; Agricultural output; Electricity production